Peranan Struktur Modal, Net Financing, Profitabilitas dan Likuiditas pada Kualitas Laba Perusahaan Properti - Suhendra suhendra (Ma'soem University, 2022)
This study aims to examine and analyze the effect of capital structure, net financing, profitability, and liquidity on earning quality. This study uses data from property companies in Indonesia for the period 2013-2018 with 20 samples of companies. In this study, capital structure is calculated based on the capital structure using financial leverage measure with the formula debt to equity ratio. Net financing is measured using net equity in the current period less current debt to total assets in the previous period. Profitability is measured using return on equity, current asset ratio is used for liquidity. Earnings quality is calculated based on the earnings response coefficient. The results show that capital structure has a positive effect on earnings response coefficient, net financing has no effect on earnings response coefficient, profitability has a positive effect on earnings response coefficient and liquidity has no effect on the earnings response coefficient. Capital structure and profitability have a positive effect on earnings quality, with this condition company needs to focus on how to manage capital structure and focus on profitability to keep maintain earnings quality. Net financing and liquidity have no effect on earnings quality, have a meaning the company that has a good capital structure and profitability, will impact to a good capability to cover the liquidity and manage asset, debt, and net worth.